The European Union’s science, technology and innovation development policy to respond to the challenges of the new context - Hoa Huu Cuong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Summary: In the context of a rapidly changing world due to global challenges such as the COVID pandemic, geopolitical competition among major powers, the Russia-Ukraine conflict, and, especially, the explosion of the Fourth Industrial Revolution has greatly affected the development of countries and regions around the world. Meanwhile, the European Union (EU) is lacking the motivation to innovate and facing many environmental and social challenges. In addition, the EU is lagging behind other countries, specifically: Losing to the United States in knowledge-based industries and the number of high-tech human resources; Being surpassed by Japan and South Korea in the high-tech product market; Facing great competitive pressure from China and India, which have increased in high-value-added industries based on cheap human resources. Recognizing this new context, the EU has implemented many measures to develop science, technology and innovation (STI). The EU's experience is a valuable suggestion for Vietnam in its implementation of STI development policies. Code: 24102101